2014
DOI: 10.1007/s00128-014-1370-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the Dispersant Corexit 9500 to Early Life Stages of Blue Crab, Callinectes sapidus

Abstract: The Deepwater Horizon well released 4.4 million barrels of light crude oil offshore of Louisiana into one of the world's largest and most productive blue crab (Callinectes sapidus) fisheries. The objectives of this paper were to determine the toxicity of the dispersant Corexit(®) 9500A used in the 2010 oil spill on juvenile and larval blue crabs, and the long-term effects of sublethal acute exposure. Only the highest treatment levels of dispersant significantly increased mortality in larval and juvenile blue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our second assumption, that oil or oil-dispersant mixture had negative effects on Blue Crab larvae, could be false if Blue Crab larvae are highly tolerant or if oil concentrations in the surface waters were not high enough to cause immediate harm. Even though several studies have shown that oil-dispersant mixtures are toxic to Blue Crab juveniles, megalopae and zoeae [ 6 9 ], juvenile crabs are relatively highly tolerant of oil or dispersant compare to other estuarine organisms [ 39 , 40 ] and near-surface zooplankton communities have been observed to recover quickly post DWH spill [ 41 ]. This suggests that toxic levels oil-dispersant mixtures either never manifested during the spill [ 9 ] or were quickly diluted, either by wave action or by rapid microbial degradation, thereby only affecting larvae that were immediately present at the time of dispersant application.…”
Section: Discussionmentioning
confidence: 99%
“…Our second assumption, that oil or oil-dispersant mixture had negative effects on Blue Crab larvae, could be false if Blue Crab larvae are highly tolerant or if oil concentrations in the surface waters were not high enough to cause immediate harm. Even though several studies have shown that oil-dispersant mixtures are toxic to Blue Crab juveniles, megalopae and zoeae [ 6 9 ], juvenile crabs are relatively highly tolerant of oil or dispersant compare to other estuarine organisms [ 39 , 40 ] and near-surface zooplankton communities have been observed to recover quickly post DWH spill [ 41 ]. This suggests that toxic levels oil-dispersant mixtures either never manifested during the spill [ 9 ] or were quickly diluted, either by wave action or by rapid microbial degradation, thereby only affecting larvae that were immediately present at the time of dispersant application.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the oil surface area, dispersants accelerate oil biodegradation by hydrocarbon-degrading bacteria (Lee 2012). Dispersants may lower the overall impact of an oil spill (Lessard and DeMarco 2000) but can also enhance the bioavailability of petroleum hydrocarbons (Ramachandran et al 2006), increasing the risk to benthic and coastal habitats (Anderson Lively and McKenzie 2014). Current and tidal movement may transport dispersants into sensitive coastal habitats such as mangroves and salt marshes where dispersed oil molecules may become trapped and concentrate within semienclosed coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the third-generation dispersants have little toxic effects on aquatic organisms, dispersing the oil spill to form small oil droplets which are more soluble and degradable in the sea. However, the results of some studies have shown that dispersants have potential to increase the bioavailability of PAH to marine organisms (Almeda 2014, Lively et al 2014, Goodbody-Gringley et al 2013. Some reports show that dispersants do not increase oil toxicity (Dussauze et al 2014, Hemmer et al 2011, Long et al 2002, but several others show that they make the effects of oil spills even worse (Milinkovitch et al 2011, Mu et al 2014, Rico-Martínez R et al 2013).…”
Section: Introductionmentioning
confidence: 99%